Deliberate Numerical Discrepancy of Generation in the Genealogy of Matthew. (3rd July 2018) - Zeng, Sha
ABSTRACT: In the genealogy of Matthew, there is a numerical 'discrepancy' between the actual totals of generations (fourteen, fourteen, and thirteen) recorded in Matthew 1:12-16 and the stated totals (fourteen, fourteen, and fourteen) in 1:17. This paper argues that Matthew's genealogy is devised by inserting breaks based on the pattern and concept of Chronicles in order to convey the unique Matthean message. This argument will be defended by showing the similarities between Chronicles and Matthew: (1) Matthew follows the Chronicler by putting the genealogy at the beginning of the whole book as an introduction to convey the Matthean messages; (2) by combining concepts of kingship and priesthood; (3) by mentioning 'the sons of Israel' and 'all Israel'; (4) by including Gentiles; (5) by using retribution theology; (6) by employing intensification in his chiastic genealogical structure; (7) Matthewâ..s omission of several kings is in line with the Chronicler's ideology of cultic-oriented kingship; (8) Matthew shares the Chronicler's point of view that Judah's deportation to Babylon does not invalidate Yahweh's promise for the Davidic kingdom. Thus, the apparent numerical 'discrepancy' is deliberately devised by the Matthean author, just as the Chronicler uses the numerical discrepancy to highlight his emphases in the genealogies.